Landscapes in Transition - Finlayson, B.; Warren, Graeme (Council for British Research in the Levant, 2010)
This volume presents a collection of papers focusing on archaeological approaches to landscape in the context of the adoption of agriculture in Southwest Asia and Northwest Europe. Case studies are presented from these contrasting regions, one where the transition to farming is indigenous, and the other where the transformation is initiated externally. This allows us to consider to what extent hunter-gatherer and farmer landscapes may be different, or the degree to which apparent differences have been constructed by our expectations and traditions of interpretation. While the concept 'landscape' enjoys considerable popularity in archaeological interpretation, it is somewhat ill-defined and inconsistently used. Some have suggested that this fluidity allows landscape to be a 'usefully ambiguous concept' but at times there is a danger that this very ambiguity affords imprecision in our narratives. This is particularly important where differing traditions of archaeological interpretation meet, as, for example, in the transition from hunting and gathering to farming. The transition has been understood as a major division in archaeological practice and attitudes to 'landscape' across the transition reflect this dichotomy. The results of these debates are illuminating, and raise questions beyond the immediate geographical scope of the volume. The contrast between the two regions provides valuable comparisons between traditions of archaeological theory and interpretation and the bodies of evidence.